LOCAL, REGIONAL, AND CORRELATION SCHEMES FOR THE PRECAMBRIAN OF KARELIA AND KOLA PENINSULA: THE HISTORICAL-METHODOLOGICAL ANALYSIS - Negrutsa V.Z. (My University, 1997)
Stratigraphic investigations of the Precambrian in Karelia and the Kola Peninsula, which are the type area for the pre-Riphean part of the Proterozoic of northern Eurasia, demonstrate a priority of local stratigraphic scales over regional and interregional schemes and the prime significance of stratotypes of stratigraphic units and their boundaries for substantiating scales of any rank. Data on the structure and subdivision of three pre-Riphean complexes (Saamian, Lopian, and Karelian) of the eastern Baltic Shield are summarized, and a system of subordinate regional subdivisions of two upper complexes assigned to the Upper Archean and the Lower Proterozoic is considered. Attempts to substantiate the event-reflecting boundaries of these subdivisions by isotopic-geochronological data are discussed. The previous studies resulted in the elaboration of the regional chronometric scale only for the Karelian, corresponding to the middle part of the general Precambrian sequence in the region. This scale should be improved in parallel with the regional chronostratigraphic scale.
Keywords: Precambrian; Precambrian; Докембрий